PENGUKURAN INDEKS KEPUASAN PELANGGAN UNTUK PENINGKATAN KUALITAS LAYANAN - Nurfarida, Iva Nurdiana (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2015)
Customer satisfaction index (CSI) can be used by companies as a measure of the level of customer satisfaction. CSI also be used to compare the performance of products/services with competitors. CSI measurement results can be used to set a strategy to improve the quality of services in order to increase customer satisfaction in the future. Some CSI measurement model has been applied in previous studies, but all have the same focus, comparing the value to the customer expectations. This research use Importance-Performance (IP) Analysis model to measure the level of customer satisfaction of PDAM Malang Regency. IP-Analysis will give information about elements are a priority, what elements need to be maintained, the element that is not a priority to be addressed, and that high last element that has been good, but not an important element for customers. The results showed that the priority of the elements that must be addressed by PDAM Malang Regency to improve customer satisfaction is about the terms of service, fairness in service, as well as courtesy and hospitality.